Universal monoclonal antibody-based influenza hemagglutinin quantitative enzyme-linked immunosorbent assay. Issue 11 (7th March 2019) - Chae, Wonil; Kim, Paul; Hwang, Beom Jeung; Seong, Baik Lin
Highlights: We developed a novel HA quantitative ELISA as an alternative for SRID. The ELISA uses broadly reactive group-specific universal mAbs. The assay is less time-consuming than the SRID assay. The assay has good accuracy, specificity, sensitivity and reproducibility. The assay performs better than SRID in terms of accuracy and sensitivity. Abstract: Seasonal and pandemic influenza infections remain a serious public health concern. Many health authorities recommend annual vaccination as the most effective way to control influenza infection. Accordingly, regulatory guidelines ask vaccine manufacturers to determine vaccine potency at the time of release and throughout shelf-life to ensure vaccine quality. The potency of inactivated influenza vaccine is related to the quantity of hemagglutinin (HA). Since 1970s, single radial immunodiffusion (SRID) assay has been standardly used for the quantitation of HA in influenza vaccine. However, SRID is labor-intensive, inaccurate, and requires standard reference reagents that should be updated annually. Therefore, there have been extensive efforts to develop alternative potency assays. In this study, we developed and tested a new HA quantitative enzyme-linked immunosorbent assay (ELISA) using a universal monoclonal antibody that can bind to HAs from various subtypes in group 1 influenza A virus (IAV). We analyzed the conserved stalk domain of HA via a library approach to design a consensus HA antigen for group 1 IAV. The antigens were expressed as a soluble form in E. coli and were purified by Ni-affinity chromatography. When tested with variety of HAs from IAVs or influenza B viruses (IBVs), the mAbs exhibited specific binding to group 1 HAs, with potential exception to H9 subtype. Among various conditions of pH, urea, and reducing agents, pretreatment of HA at low pH exposing the conserved stalk domain was crucially important for optimal ELISA performance. Calibration curves for various HAs were generated to determine accuracy, specificity, sensitivity, and linear dynamic range. The ELISA method shows high sensitivity and accuracy compared with the SRID assay. The HA group specific universal mAbs against the consensus stalk domain of HA are conducive to establishing an ELISA-based standard procedure for the quantitation of HA antigens for annual vaccination against influenza infection.